Developing a validated hydrocode model for adobe under impact loading. (June 2017) - Sauer, Christoph; Heine, Andreas; Riedel, Werner
Highlights: We develop a validated hydrocode model for impact loading of adobe. In this model, strength and failure depend on pressure, Lode angle, and strain rate. Employed material parameters originate from test data and engineering assumptions. Including porosity in the equation of state is found to be crucial. Ballistic experiments are quantitatively reproducible with a unified parameter set. Abstract: We present hydrocode simulations of penetration and perforation of adobe targets by high-hardness spherical steel projectiles. For the description of adobe we employ the RHT concrete model, which describes strength and failure depending on pressure, Lode angle, and strain rate in combination with a porous equation of state. In order to apply this model to adobe we develop a parameter set partially based on material test data. Other parameters are obtained through engineering assumptions, and their importance is assessed by sensitivity analyses. Ballistic reference experiments are reproduced well by our simulations especially regarding residual velocities of projectiles perforating finite-thickness targets. Therein, we also properly capture the deformation of the projectile and the damage of the target. Simulations of the penetration into semi-infinite targets are in acceptable agreement with the ballistic data. However, a significant influence of target setup and boundary conditions on the resulting penetration depths is discovered. The residual velocities obtained by perforation simulations do not show such sensitivity but considerably depend on the yielding threshold of the projectile. Hence, the latter property of the projectile must be correctly included in the simulation in order to be able to draw conclusions on the ability of the material model and the model parameters to describe the target. As for other building and geological materials, the pore compaction is revealed to be an important form of energy dissipation also for adobe and is hence an essential ingredient for the description of the ballistic performance of this material.